Allocating Tax Revenue to Sub-Central Government Levels: Lessons from Germany and Poland - Malgorzata Magdalena Hybka (Institute of Economic Research (IER), 2015)
Tax sharing arrangements provide considerable financial resources to sub-central government levels. This statement is true both for unitary and federal states although tax revenue sharing mechanisms differ significantly across countries. The basic aim of this article is to compare the mechanisms adopted in Germany and in Poland. It assesses the degree of tax autonomy granted to sub-central government levels in the countries analysed, overviews the principles of apportionment of joint (shared) taxes and presents statistics on tax revenue composition of sub-central government levels.
Keywords: H2; H7; 330; apportionment of tax revenue; fiscal federalism; Germany; Poland